HistomicsTK: A Python toolkit for pathology image analysis algorithms - Pourakpour, Fattaneh; Szölgyén, Ákos; Nateghi, Ramin; Gutman, David A; Manthey, David; Cooper, Lee AD (SoftwareX, 2025)
Growth in the digital imaging of glass tissue slides has produced petabytes of data, however, this data remains underutilized in biomedical research due in part to a lack of open-source software. HistomicsTK is an open-source Python package that provides preprocessing, segmentation, and feature extraction capabilities for building histology image processing pipelines. HistomicsTK can function as a standalone Python package or serve containerized pipelines through a web-based interface using the Digital Slide Archive platform. This paper provides an overview of HistomicsTK with illustrative use cases and describes how this project engages the community in software development and maintenance.